Corporate consequences liabilities, penalties, actions, and sanctions under the revised Corporation Code - Guerrero, George Mitchell S. (2019)
Republic Act No. 11232 (2019) signed earlier this year marks the culmination of a multi-year recodification resulting in the Revised Corporation Code. In many respects, it retained the key principles of private corporation law in effect since colonial times. However, there are key facets which underwent a reimagination - a paradigm shift in underlying assumptions, inasmuch as a textual change. Two aspects stand out in the review of pre-revision characteristics: an exclusivity in jurisdiction and exclusivity in consequences. Altering the statutory language may have changed the dynamics of jurisdiction between the bodies that exercise it - the courts and the Securities and Exchange Commission - but the animating principle remained the same. Jurisdiction of one tribunal over a remedy (and corresponding consequence) excludes the other. However, the same cannot be said for liabilities, penalties, sanctions, and agency actions. Codal text, legislative history, and public policy reveals the abandonment of the rule of preclusion by civil and administrative consequences of the criminal consequences laid down in Ient v. Tullet Prebon (Phils.), Inc. In doing so, Congress has strengthened accountability mechanisms, increased regulatory flexibility, and prevents escape from liability without sacrificing conformity with the requirements of due process.
Keywords: Corporation law